Pneumonia in mechanically ventilated patients: no diagnostic and prognostic value of different quantitative tracheal aspirates thresholds. Issue 1 (2nd January 2018) - Garnacho-Montero, J.; Gutiérrez-Pizarraya, A.; Lopez-García, I.; Miranda, J. C.; González-Galán, V.; Corcia-Palomo, Y.; Alonso-Araujo, I.; Martín-Villén, L.; Aznar-Martín, J.; Amaya-Villar, R.
Abstract: Background: Diagnosis of pneumonia in ventilated patients is challenging due to the lack of specific and definitive clinical symptoms, laboratory data or radiological abnormalities. Methods: Based on quantitative tracheal aspirate (QTA) results, three groups of patients were compared: <10 5 cfu/ml, ≥10 5 cfu/ml and <10 6 cfu/ml, and ≥10 6 cfu/ml. We recorded demographic variables, underlying diseases and severity of illness at ICU admission. On the day of pneumonia diagnosis, we registered temperature, leukocyte count, C-reactive protein, Sequential Organ Failure Assessment (SOFA) score, clinical pulmonary infection score (CPIS) and adequacy of empirical antimicrobial therapy. Results: In 231 episodes, clinical presentation, laboratory data, severity of illness, CPIS, the presence of bacteremia and radiological score did not differ among the three groups. ICU and hospital mortalities were also similar in the three groups. Factors independently associated with in-hospital mortality were age, SOFA score and inappropriate antimicrobial therapy. The bacterial burden in the QTA was not included in the model. Conclusions: Quantification of tracheal aspirate samples may not be necessary in ventilated patients clinically suspected of having nosocomial pneumonia